Food hygiene and sanitation assessment at Brahim’s Sats Food Services Sdn. Bhd. / Asiah Mardiah Mohamed & Nur Adlia Razmi - Mohamed, Asiah Mardiah; Razmi, Nur Adlia (2017)
This study was conducted in airline catering at Brahim’s SATS Food Service Sdn. Bhd. (BSFS) to assess compliance level and degree of food hygiene and sanitation practices based on Food and Drug Administration (FDA) 2004 guidelines. The study incorporated onsite observations, field assessments, and interviews to verify the current states and practices. The modified auditing form based on Ministry of Health (MOH) Ordinance Food Premises Hygiene under sections 10 and 11 of the Food Act 1983 are used. The five factors that are considered during assessment and observation are food and beverages, food handler practices, equipment used, facilities provided and others that are related to food hygiene and sanitation assessment at food premises. Overall results showed that all three-different kitchens such as cold kitchen, pastry kitchen, and hot kitchen are complied with FDA 2004 guidelines, which received above 80%. The cold kitchen is the highest compliance level with 97.5%; followed by pastry kitchen with 96% and hot kitchen with 95.5%.